Developing CAD-Based Learning Module on Manufacturing Engineering Drawing - Nendra, Fadly; Syahril, Syahril; Abdullah, Rijal; Jamilah, Yumn; Netriwati, Netriwati; Aini, Nur Rohmatul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
This research aims to develop a learning module on Manufacturing Engineering Drawings that are interesting and appropriate for use in learning, to learn the practicality of module in the learning process, and to find out the learning module in improving student learning outcomes. The design of research and development used as a 4D (Define, Design, Develop, and Dissemination) development model. The results obtained from the study of this development as follows: (1) to generate a Computer-Aided Design (CAD)-based learning module, (2) the validity of the module was declared valid by media experts (0.89), subject matter experts (0.88), and linguists (0.85), (3) based on the response of teachers, the module was very practical (90.64 %) and based on student’s responses, the module was declared as very practical (84.65 %), (4) the module was declared effective and can improve learning outcomes of students. Based on the findings of this study, it can be concluded that the developed learning module is valid, practical, and effective to be used as a learning module in Manufacturing Engineering Drawing.